2016
DOI: 10.1155/2016/5474837
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Phase Inflammatory Response to Single-Bout HIIT and Endurance Training: A Comparative Study

Abstract: Objective. This study compared acute and late effect of single-bout endurance training (ET) and high-intensity interval training (HIIT) on the plasma levels of four inflammatory cytokines and C-reactive protein and insulin-like growth factor 1. Design. Cohort study with repeated-measures design. Methods. Seven healthy untrained volunteers completed a single bout of ET and HIIT on a cycle ergometer. ET and HIIT sessions were held in random order and at least 7 days apart. Blood was drawn before the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
2
32
1
1
Order By: Relevance
“…; Kaspar et al. ). Moreover, the distinctly downregulated KEGG pathway Steroid hormone biosynthesis might be the linked to the observed inhibition of JAK‐STAT associated hormone expression, as previously reported (Gupta and Mayer ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…; Kaspar et al. ). Moreover, the distinctly downregulated KEGG pathway Steroid hormone biosynthesis might be the linked to the observed inhibition of JAK‐STAT associated hormone expression, as previously reported (Gupta and Mayer ).…”
Section: Resultsmentioning
confidence: 98%
“…; Kaspar et al. ). Taken together, it is possible to use the aforementioned molecular biomarkers in combination with specific metabolic parameters (such as heart rate, respiratory gas exchange, mitochondrial function, and energy metabolism) to monitor and study HIIT‐induced effects (Gibala et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The (MCP-1/IGF-1)*IL-6 while not significant did trend upwards throughout the four groups, whereas the (MCP-1/IGF-1)*IL-1β ratio appeared to trend down with the obese group and upwards with the diabesity group. We have previously observed significant differences in IL-6/IL-10, as a measure of the pro/anti-inflammatory response in endurance training and high intensity interval training when compared to a control group [49]. Our own work on mild cognitive decline also suggests that the interaction between IL-6 and IL-10 measured as a ratio is part of the pathophysiological process [50].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, HIIT sessions take not more than 20 min and have been shown to be equally or even more effective in inducing cardiovascular adaptations (Gibala et al 2012) and improving performance (Milanović et al 2015) compared to moderate-intensity continuous exercise. Investigating the acute inflammatory response, Leggate et al (2010) and Wadley et al (2015) showed that the increase in IL-6 after HIIT was greater compared to moderate-intensity continuous exercise, although this finding has not consistently been shown in the literature (Cabral-Santos et al 2015;Kaspar et al 2016).…”
Section: Introductionmentioning
confidence: 98%